2004
DOI: 10.1038/sj.cr.7290201
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MRP14 gene is frequently down-regulated in Chinese human esophageal cancer

Abstract: Migration inhibitory factor-related protein 14 (MRP14) is one of calcium-binding proteins, referred as S100A9. The heterodimeric molecule formed by MRP14 with its partner MRP8 (S100A8) is the major fatty acid carrier in neutrophils. The MRP8/14 complex has been also implicated in the intracellular transport of arachidonic acid and its precursors in keratinocytes. We show here the involvement of MRP14 in human esophageal cancer. In an initial study, mRNA differential display -reverse transcription polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
3
27
0
Order By: Relevance
“…The present work indicates that protein S100A9 is up-regulated in 59.65% of the ESCC samples and down-regulated only in 10.17% of the ESCC cases. However, reduction of S100A9 expression is a frequent finding in Chinese human esophageal adenocarcinoma cancer [36,37]. This difference may arise from variations in the sample group, such as pathological typing and TNM stage, among others.…”
Section: Discussionmentioning
confidence: 94%
“…The present work indicates that protein S100A9 is up-regulated in 59.65% of the ESCC samples and down-regulated only in 10.17% of the ESCC cases. However, reduction of S100A9 expression is a frequent finding in Chinese human esophageal adenocarcinoma cancer [36,37]. This difference may arise from variations in the sample group, such as pathological typing and TNM stage, among others.…”
Section: Discussionmentioning
confidence: 94%
“…Although in squamous cell esophageal carcinomas, the loss of S100A8 and S100A9 is very well documented. 29 It has also been shown that the S100A9 levels correlate with the extent of tumor differentiation. 30 In a recent study, we have demonstrated that annexin A1, a potential tumor suppressor is an in vivo target of miR-196a in EA.…”
Section: Discussionmentioning
confidence: 99%
“…They could resist microorganisms, induce apoptosis, and are the markers for various inflammatory diseases [10]. Recent studies demonstrate decreased expression of S100A8/A9 heterodimer in various squamous epithelial tumors (e.g., esophageal squamous carcinoma and head/neck squamous carcinoma) [11,12], consistent with a role of the heterodimer in the pathogenesis of squamous carcinomas. However, the expression of S100A8/A9 increases in various gland cell tumors and is associated with low differentiation of tumors [13,14].…”
Section: Introductionmentioning
confidence: 92%